SEMANGAT TOLERANSI SANTRI MILENIAL (STUDI KASUS DI PONDOK PESANTREN ROUDHOTUS SHOLIHIN, DEMAK) - Nicolas Eka Novian Wicaksono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2022)
This study aims to determine, describe, and analyze the role of pesantren in implementing the spirit of tolerance of the millennial generation santri in traditional pesantren as a resolution of the turbulence of globalization. The method used in this research is qualitative. Data collection techniques using observation and interviews. The research location is the Roudhotus Sholihin Sayung Islamic Boarding School, Demak. The results of this study are the students of this traditional Islamic boarding school have a spirit of tolerance which is marked by their knowledge of the position of Pancasila as the basis of the state. The students are also able to practice the precepts in Pancasila, have knowledge of the concept and meaning of Bhinneka Tunggal Ika, respect differences, use the Indonesian language, respect the flag, maintain the integrity of the country, and ward off radicalism and terrorism. The role of Islamic boarding schools in implementing the spirit of tolerance is the implementation of the commemoration of the independence of the Republic of Indonesia, the distribution of students' bedrooms fairly, the use of Indonesian language, the implementation of grave pilgrimages, and the commemoration of religious holidays. Pesantren's efforts in maintaining the Unitary State of the Republic of Indonesia and building the spirit of nationalism are communication media literacy, revitalization of pesantren discipline, organizing bahsul masail, and socializing the vision and mission of the pesantren